Comparing Public-Versus-Private Sector Pay and Benefits: Examining Lifetime Compensation. (December 2013) - Reilly, Thom
The large unfunded liabilities surrounding public pensions in the United States will ensure the issue of comparable pay between the public and private sectors remains in the forefront of public policy debates. Disagreements on pay and total compensation comparison studies vary due to different approaches, methods and data. In an effort to add to the literature on comparative compensation, a public-versus-private sector compensation model was constructed to gauge the cost of lifetime compensation. This analysis considers three types of workers within two different occupations classifications: a private sector employee with a traditional 401(k) retirement package offering, a public sector employee who has a defined benefit plan with social security income, and a public sector worker with no social security income. The two sample occupations reviewed as part of this analysis focus on administrative assistants (blue-collar workers) and engineers (white-collar employees) to provide alternatives for evaluation purposes. For the two occupation scenarios analyzed, total compensation of public employees is higher than that of an average private sector employee. When the total compensation is based on years worked, the divide between the public and private sectors increases significantly. In light of this analysis, several important public policy issues are advanced.